علاقة الرؤى والأحلام بالنبوات عند مفكري الإسلام: Visions and Dreams and their connection to Prophethood in Islamic Thought - الجندي محمد علي (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2013)
تهدف هذه الدراسة إلى تعرّف أبعاد العلاقة القائمة بين الرؤى والأحلام وصلتها بالنبوات في الفكر الإسلامي. ولتحقيق هذا الهدف، فقد اتجهت الدراسة إلى تتبع منابع هذه الجدلية في الفكر الشرقي القديم، ثم في الفكر اليوناني، ثم انتقال هذه المنابع وأثرها في عرض مفردات هذه الجدلية عند مفكري الإسلام من متكلمين وفلاسفة ومتصوفة. وتعمد الدراسة إلى إبراز الجانب المتعلق بالإسهام الإسلامي بصورة مفصّلة، لبيان حجية الرؤى والأحلام، وصلتها بالنبوة، ومدى توافقها مع الكتاب وصحيح السنة، ولتؤسس لنا -في الوقت نفسه- منطلقات علمية ومنهجية لفهم هذا الموضوع الشائك، الذي يدخل في دائرة دراسة الغيبيات. This study aims to explore the connecting dimension, between visions and dreams and their connection to Prophethood in Islamic thought. To achieve this aim, the study had reviewed the sources of the debate on this issue, including the oriental religious thought, Greek thought, and their effects upon Muslim theologians, philosophers and sophists). The study also discusses Islamic contribution thoroughly to show how visions and dreams were presented in the noble Quran and authentic Sunna of the Prophet, and to lay down a knowledge base and methodology to understand this issue that is part of unseen domain.